Pengaruh Pemberian Pendidikan Kesehatan Dengan Metode Story Telling Terhadap Tingkat Pengetahuan Kebersihan Gigi Pada Anak Usia Sekolah Di Sdn Inpres Kala - Ayatullah Ayatullah; Wahidah Wahidah (Barongko: Jurnal Ilmu Kesehatan, 2022)
Dental and oral health is part of physical health that cannot be separated from one another because it will affect the body as a whole (Lossu et al 2015). This study aims to determine the effect of providing health education using the story telling method on the level of dental hygiene knowledge of school children at SDN Inpres Kala in 2022. The experimental research form used in this study was a one group pretest-posttest design. The results of the study obtained data that there was an effect of story telling education on the level of knowledge of dental hygiene, there was a difference between the level of dental hygiene before and after giving the story telling method. There was a significant effect through the provision of the story telling method on the level of knowledge of dental hygiene at SDN Inpres Kala where the value of p = 0.037. Data analysis using the SPSS 16.0 for Windows computer program. Prior to receiving health education through the story telling method, most school children at SDN Inpres Kala had a moderate level of dental hygiene knowledge. After receiving health education through the story telling method, most school children at SDN Inpres Kala have a high level of dental hygiene knowledge. There is an effect of health education through the story telling method which is significant on the level of dental hygiene knowledge of school children at SDN Inpres Kala (p=0.037;p<0.05)